Optimal Scaling of Aftershock Zones using Ground Motion Forecasts - John Max Wilson; Mark R. Yoder; John B. Rundle (Pure and Applied Geophysics, 2018)

Earthquakes and Multi-hazards around the Pacific Rim, Vol. 1: Introduction - Yong-Xian Zhang; Thomas Goebel; Zhigang Peng; Charles Williams; Mark Yoder; John Rundle (Pure and Applied Geophysics, 2017)

Parametrizing Physics-Based Earthquake Simulations - Kasey W. Schultz; Mark R. Yoder; John M. Wilson; Eric M. Heien; Michael K. Sachs; John B. Rundle; Don L. Turcotte (Pure and Applied Geophysics, 2017)

Spatial Evaluation and Verification of Earthquake Simulators - John Max Wilson; Mark R. Yoder; John B. Rundle; Donald L. Turcotte; Kasey W. Schultz (Pure and Applied Geophysics, 2017)

Erratum to: A novel approach for the development of tiered use biological criteria for rivers and streams in an ecologically diverse landscape - R. William Bouchard; Scott Niemela; John A. Genet; Chris O. Yoder; John Sandberg; Joel W. Chirhart; Mike Feist; Benjamin Lundeen; Dan Helwig (Environmental Monitoring and Assessment, 2016)

A novel approach for the development of tiered use biological criteria for rivers and streams in an ecologically diverse landscape - R. William Bouchard; Scott Niemela; John A. Genet; Chris O. Yoder; John Sandberg; Joel W. Chirhart; Mike Feist; Benjamin Lundeen; Dan Helwig (Environmental Monitoring and Assessment, 2016)

Record-Breaking Intervals: Detecting Trends in the Incidence of Self-Similar Earthquake Sequences - Mark R. Yoder; John B. Rundle (Pure and Applied Geophysics, 2015)

E-DECIDER: Using Earth Science Data and Modeling Tools to Develop Decision Support for Earthquake Disaster Response - Margaret T. Glasscoe; Jun Wang; Marlon E. Pierce; Mark R. Yoder; Jay W. Parker; Michael C. Burl; Timothy M. Stough; Robert A. Granat; Andrea Donnellan; John B. Rundle; Yu Ma; Gerald W. Bawden; et al. (Pure and Applied Geophysics, 2015)

Near-Field ETAS Constraints and Applications to Seismic Hazard Assessment - Mark R. Yoder; John B. Rundle; Margaret T. Glasscoe (Pure and Applied Geophysics, 2015)

The Feasibility and Educational Value of Hear My Voice, a Chaplain-Led Spiritual Life Review Process for Patients with Brain Cancers and Progressive Neurologic Conditions - Katherine M. Piderman; Carmen Radecki Breitkopf; Sarah M. Jenkins; Laura A. Lovejoy; Yvette M. Dulohery; Dean V. Marek; Heidi L. Durland; Debra L. Head; Spence W. Swanson; James T. Hogg; John L. Evans; Scott E. Jorgenson; et al. (Journal of Cancer Education, 2015)

BioEarth: Envisioning and developing a new regional earth system model to inform natural and agricultural resource management - Jennifer C. Adam; Jennie C. Stephens; Serena H. Chung; Michael P. Brady; R. David Evans; Chad E. Kruger; Brian K. Lamb; Mingliang Liu; Claudio O. Stöckle; Joseph K. Vaughan; Kirti Rajagopalan; John A. Harrison; et al. (Climatic Change, 2015)

Differential expression and ligand binding indicate alternative functions for zebrafish polymeric immunoglobulin receptor (pIgR) and a family of pIgR-like (PIGRL) proteins - Amanda N. Kortum; Ivan Rodriguez-Nunez; Jibing Yang; Juyoung Shim; Donna Runft; Marci L. O’Driscoll; Robert N. Haire; John P. Cannon; Poem M. Turner; Ronda T. Litman; Carol H. Kim; Melody N. Neely; et al. (Immunogenetics, 2014)

Statistical Variability and Tokunaga Branching of Aftershock Sequences Utilizing BASS Model Simulations - Mark R. Yoder; Jordan Van Aalsburg; Donald L. Turcotte; Sergey G. Abaimov; John B. Rundle (Pure and Applied Geophysics, 2013)

Amyloid pathway-based candidate gene analysis of [11C]PiB-PET in the Alzheimer’s Disease Neuroimaging Initiative (ADNI) cohort - Shanker Swaminathan; Li Shen; Shannon L. Risacher; Karmen K. Yoder; John D. West; Sungeun Kim; Kwangsik Nho; Tatiana Foroud; Mark Inlow; Steven G. Potkin; Matthew J. Huentelman; David W. Craig; et al. (Brain Imaging and Behavior, 2012)

Evidence for a transposition event in a second NITR gene cluster in zebrafish - Jeffrey A. Yoder; John P. Cannon; Ronda T. Litman; Carly Murphy; Jennifer L. Freeman; Gary W. Litman (Immunogenetics, 2008)

No evidence for root-mediated allelopathy in Centaurea solstitialis, a species in a commonly allelopathic genus - Bo Qin; Jennifer A. Lau; Joseph Kopshever; Ragan M. Callaway; Heather McGray; Laura G. Perry; Tiffany L. Weir; Mark W. Paschke; Jose L. Hierro; John Yoder; Jorge M. Vivanco; Sharon Strauss (Biological Invasions, 2007)

Immunoglobulin variable regions in molecules exhibiting characteristics of innate and adaptive immune receptors - Gary W. Litman; John P. Cannon; Larry J. Dishaw; Robert N. Haire; Donna D. Eason; Jeffrey A. Yoder; Jose Hernandez Prada; David A. Ostrov (Immunologic Research, 2007)

A model for pro‐poor wealth creation through small‐plot irrigation and market linkages - John Magistro; Michael Roberts; Steve Haggblade; Fritz Kramer; Paul Polak; Elizabeth Weight; Robert Yoder (Irrigation and Drainage, 2007)
This paper relates the field experience of an international NGO in strengthening linkages between irrigation development and poverty reduction. Poverty Reduction through Irrigation and Smallholder Markets (PRISM) is introduced as a methodology for combining small‐plot irrigation technology with complementary inputs and services to enhance small farmers' ability to participate effectively in markets for high‐value agricultural commodities. Data from field projects in Nepal and India indicate that the PRISM approach can lead to significant additional income for small farmers and other micro and small enterprises in agricultural value chains. Copyright © 2007 John Wiley & Sons, Ltd.

Agrobacterium tumefaciens and Agrobacterium rhizogenes transformed roots of the parasitic plant Triphysaria versicolor retain parasitic competence - Alexey Tomilov; Natalya Tomilova; John I. Yoder (Planta, 2007)

Relationships of Exodontiella , a non‐alysiine, exodont member of the family Braconidae (Insecta, Hymenoptera) - Robert A. Wharton; Matthew J. Yoder; Joseph J. Gillespie; John C. Patton; Rodney L. Honeycutt (Zoologica Scripta, 2006)
The placement of Exodontiella Wharton is re‐examined in light of the discovery of four additional individuals. Genomic DNA was extracted from one of the individuals, the D2 expansion segment of the 28S rRNA gene was sequenced, and the sequence compared to selected taxa within the Braconidae. Based on the molecular data and the morphological study, Exodontiella is formally transferred from the Opiinae to the Gnamptodontinae. The genus and its included species are redescribed.

Modeling Ocean Ecosystems: The PARADIGM Program - Lewis Rothstein; John Cullen; Mark Abbott; Eric Chassignet; Ken Denman; Scott Doney; Hugh Ducklow; Katja Fennel; Mick Follows; Dale Haidvogel; Eileen Hofmann; David Karl; et al. (Oceanography, 2006)

In Vitro Haustorium Development in Roots and Root Cultures of the Hemiparasitic Plant Triphysaria Versicolor - Alexey Tomilov; Natalia Tomilova; John I. Yoder (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Climatological phytoplankton chlorophyll and sea surface temperature patterns in continental shelf and slope waters off the northeast U.S. coast - James A. Yoder; Stephanie E. Schollaert; John E. O'Reilly (Limnology and Oceanography, 2002)
Satellite‐derived chlorophyll estimates from the Sea‐viewing Wide Field‐of‐view Sensor (SeaWiFS) and Coastal Zone Color Scanner (CZCS), a large archive of in situ near‐surface chlorophyll data, and satellite sea surface temperature (SST) measurements were used to quantify spatial and seasonal variability of near‐surface chlorophyll and SST in middle shelf to slope waters off the coast of the U.S. Northeast. The results of empirical orthogonal function (EOF) analysis on normalized monthly fields (after temporal and spatial means were removed) show that all three chlorophyll climatologies have similar mode 1 temporal and spatial patterns in these waters. Mode 1, which explains about half of the total variability in monthly climatological images, shows that shelf waters in the Gulf of Maine (GOM) are out of phase with the mid‐Atlantic bight (MAB), with seasonally high chlorophyll concentrations in winter in the MAB and in summer in the GOM. The three chlorophyll climatologies begin to differ at higher modes (modes 2 and 3), although SeaWiFS and in situ climatologies keep similar features through mode 3. Higher modes in both SST and chlorophyll are related to the effects of tidal mixing on Georges Bank, differences in seasonal stratification between the southwestern and northeastern GOM, and the importance of the spring bloom in MAB outer shelf waters and western GOM. SST patterns during the CZCS and SeaWiFS eras are very similar, and this indicates that the observed differences between results obtained with these two sensors are probably not caused by differences in physical processes during the two satellite eras.

Enhanced chlorophyll at the shelfbreak of the Mid‐Atlantic Bight and Georges Bank during the spring transition - John P. Ryan; James A. Yoder; Peter C. Cornillon (Limnology and Oceanography, 1999)
In 8 yr (1979–1986) of Coastal Zone Color Scanner (CZCS) imagery, we find annual enhancement of chlorophyll at the shelfbreak of the Mid‐Atlantic Bight (MAB) and Georges Bank during the spring transition from well‐mixed to stratified conditions. Spatial and temporal extents of enhancement vary interannually, and expression is intermittent intraannually. This feature can span the entire MAB and southern flank of Georges Bank (∼1,100 km) and can be expressed for as long as 10 weeks (mid‐April to late June). Pigment concentrations within the feature average more than two times that of adjacent shelf and slope waters. Enhanced shelfbreak chlorophyll consistently coincided with the shelf‐slope front and often extended inshore of the surface outcrop of the front a few to ∼10 km. In all years except 1986, it coincided with seaward entrainment of shelf water by Gulf Stream warm‐core rings (WCRs) or meanders. Shelfbreak chlorophyll enhancement was most pronounced during 1980. Using satellite and in situ observations, we found that during 1980, it coincided with the shelf‐slope front for 10 weeks, and, unlike the spring bloom, it was dominated by the nanophytoplankton ( 10% of the variance about the mean. This annual biological feature, brought to light in satellite ocean color imagery, is an important aspect of the shelf‐slope ecology of the MAB and Georges Bank.

Insertional inactivation of the tomato polygalacturonase gene - Michael B. Cooley; John I. Yoder (Plant Molecular Biology, 1998)

A species-specific recognition system directs haustorium development in the parasitic plant Triphysaria (Scrophulariaceae) - John I. Yoder (Planta, 1997)